Algeria : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2002 Article IV Consultation highlights that the overall budget balance of Algeria weakened in 2001 and the first half of 2002. This deterioration mainly reflected higher spending and a decline in hydrocarbon revenues owing to a reduction in volumes and prices. The overall balance dropped from a surplus of 9.8 percent of GDP in 2000 to a surplus of 3.4 percent of GDP in 2001 and to a small deficit in the first half of 2002. Regarding structural reforms, some progress has been achieved in two areas: economic liberalization and privatization/public sector restructuring.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet